Posted by peyton on Saturday, September 24, 2011 at 5:19pm.
You are substituting for y instead of x
Besides that you were still keeping the y as well.
5(3-2y) + 4y = 8
15 - 10y + 4y = 8
-6y = -7
y = 7/6
then in x = 3-2y
x = 3-14/6 = 2/3
x = 2/3 , y = 7/6
i understand how you got the answer i just don't get why i don't put 5x+4y before the equation because i have been for all the other ones and i got those ones right..
for example this one:
i isolated the second equation into y=3+x
then i subbed in the other equation..
and i checked my answer and it was correct.
i just don't understand what i'm doing wrong for the equation.. because i keep thinking the full equation must go first not seperate it.
Horizontal line through(5,0)
maths - solve the following simultaneous equation: 5x+2y=29 x-y=-4 2x-y=-1 3x-y=...
Algebra - To solve the system of equations, which expression could be ...
Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...
Math - Solve the system by addition or substitution. 3x 4y = 8 6x ...
Algebra 1 - -3x+2y=0 -5x+2y=9 8x+4y=12 Is each equation a direct Variation? If ...
Algebra - I am re posting this for fear that it was overlooked earlier. I have ...
math,algebra - I'm not understanding so the answer should read as follows ...
math correction - solve for x: 3x - 2y = 6 i need help in solving this: the ...
HELP! - The problem using elimination/substitution methods what is the solution ...
hard math - please someone help me! i've tried so hard! factor m^6 + n^2 28x...
For Further Reading